Infrastructure regulation and poverty reduction in developing countries: a review of the evidence and a research agenda - Parker, David; Kirkpatrick, Colin; Figueira, Catarina (Elsevier Science B.V., Amsterdam., 2008)
Poverty reduction is a primary goal of development policy. In large parts of the World people have to live on meagre incomes and have limited access to infrastructure services, such as mains water, safe sanitation, mains power supplies, maintained roads and telephones. In response, more and more infrastructure provision has been opened up to private investment over the last two decades and regulatory institutions have been introduced to protect the public interest in the absence of state ownership. In this paper the role of infrastructure regulation in poverty reduction is investigated drawing on the published evidence. The conclusion is that the evidence is both patchy and sometimes contradictory. There is mixed knowledge regarding the extent to which regulators address poverty issues and about the results of regulatory decisions. The paper concludes by proposing a future research agenda aimed at improving our understanding of the ways in which infrastructure regulation impacts on poverty, with the objective of improving actual regulatory policy in developing economies.